2010
DOI: 10.21608/jfds.2010.82486
|View full text |Cite
|
Sign up to set email alerts
|

A New Pasteurized Nectars Prepared From Husk Tomato and Carrot Juices

Abstract: The present study proposed to produce a new pasteurized blended nectars from husk tomato (Physalis peruviana L.) and carrot (Daucus carota) juice in order to determine whether it could prefer to the consumer. Results showed that husk tomato juice contained high acidity,1.43% (pH, 3.79), high content of ascorbic acid (31.0 mg/100 ml) and total sugars (6.41%). Meanwhile, carrot juice contained high carotenoids content (6600µg/100ml). so, attention was paid to make use of the valuable constituents and quality att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The carotenoid content in carrot juices varies and depends on many factors, for example, type of raw material and/or storage time [ 13 ]. In this study, the highest content of carotenoids was demonstrated in juices made of orange carrot 27.50 mg/100 mL in the juice prepared by the use of HSJ and 24.69 mg/100 mL in the juice obtained by the use of LSJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carotenoid content in carrot juices varies and depends on many factors, for example, type of raw material and/or storage time [ 13 ]. In this study, the highest content of carotenoids was demonstrated in juices made of orange carrot 27.50 mg/100 mL in the juice prepared by the use of HSJ and 24.69 mg/100 mL in the juice obtained by the use of LSJ.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the highest content of carotenoids was demonstrated in juices made of orange carrot 27.50 mg/100 mL in the juice prepared by the use of HSJ and 24.69 mg/100 mL in the juice obtained by the use of LSJ. In comparison, Amal et al [ 13 ] shown that the total content of carotenoids in the juice from orange carrot was 6.6 mg/100 mL. The difference in the results may arise from the variety of carrot use in the research, growing conditioning and cultivation practice [ 14 ].…”
Section: Discussionmentioning
confidence: 99%